Phenolic compounds from the aerial parts of Clematis viticella L. and their in vitro anti-inflammatory activities*. Issue 17 (2nd September 2019) - Kırmızıbekmez, Hasan; İnan, Yiğit; Reis, Rengin; Sipahi, Hande; Gören, Ahmet C.; Yeşilada, Erdem
Abstract: Phytochemical investigations on the EtOH extract of Clematis viticella led to the isolation of six flavonoid glycosides, isoorientin (1 ), isoorientin 3′- O -methyl ether (2 ), quercetin 7- O -α-L-rhamnopyranoside (3 ), quercetin 3, 7-di- O -α-L-rhamnopyranoside (4 ), manghaslin (5 ) and chrysoeriol 7- O -β-D-glucopyranoside (6 ), one phenylethanol derivative, hydroxytyrosol (7 ), along with three phenolic acids, caffeic acid (8 ), ( E )- p -coumaric acid (9 ) and p -hydroxybenzoic acid (10 ). The structures of the isolates were elucidated on the basis of NMR and HR-MS data. All compounds were isolated from C. viticella for the first time. Compounds7 and8 showed significant anti-inflammatory activity at 100 μM by reducing the release of NO in LPS-stimulated macrophages comparable to positive control indomethacin. Compounds3 and7 exhibited anti-inflammatory activity through lowering the levels of TNF-α while1, 3 and5 decreased the levels of neopterin better than the positive controls. Abstract :